Blood-based host biomarker diagnostics in active case finding for pulmonary tuberculosis: A diagnostic case-control study. (March 2021) - Moreira, Flora Martinez Figueira; Verma, Renu; Pereira dos Santos, Paulo Cesar; Leite, Alessandra; da Silva Santos, Andrea; de Araujo, Rafaele Carla Pivetta; da Silva, Bruna Oliveira; de Sá Queiroz, Júlio Henrique Ferreira; Persing, David H.; Södersten, Erik; Gnanashanmugam, Devasena; Khatri, Purvesh; et al.
Abstract: Background: There is a need to identify scalable tuberculosis screening strategies among high burden populations. The WHO has identified a non-sputum-based triage test as a development priority. Methods: We performed a diagnostic case-control study of point-of-care C-reactive protein (CRP) and Prototype-Xpert-MTB-Host-Response (Xpert-MTB-HR) assays in the context of a mass screening program for tuberculosis in two prisons in Brazil. All incarcerated individuals irrespective of symptoms were screened by sputum Xpert MTB/RIF and sputum culture. Among consecutive, Xpert MTB/RIF or culture-confirmed cases and Xpert MTB/RIF and culture-negative controls, CRP was quantified in serum by a point-of-care assay (iChroma-II) and a 3-gene expression score was quantified from whole blood using the Xpert-MTB-HR cartridge. We evaluated receiver operating characteristic area under the curve (AUC) and assessed specificity at 90% sensitivity and sensitivity at 70% specificity, consistent with WHO target product profile (TPP) benchmarks. Findings: Two hundred controls (no TB) and 100 culture- or Xpert MTB/RIF-positive tuberculosis cases were included. Half of tuberculosis cases and 11% of controls reported any tuberculosis symptoms. AUC for CRP was 0·79 (95% CI: 0·73–0·84) and for Xpert-MTB-HR was 0·84 (95% CI: 0·79–0·89). At 90% sensitivity, Xpert-MTB-HR had significantly higher specificity (53·0%, 95% CI: 45·0–69·0%) than CRP (28·1%, 95% CI: 20·2–41·8%) ( p = 0·003), both well below the TPP benchmark of 70%. Among individuals with medium or high sputum Xpert MTB/RIF semi-quantitative load, sensitivity (at 70% specificity) of CRP (90·3%, 95% CI: 74·2–98·0) and Xpert-MTB-HR (96·8%, 95% CI: 83·3–99·9%) was higher. Interpretation: For active case finding in this high tuberculosis-burden setting, CRP and Xpert-MTB-HR did not meet TPP benchmarks for a triage test. However, Xpert-MTB-HR was highly sensitive in detecting individuals with medium or high sputum bacillary burden. Funding: National Institutes of Health (R01 AI130058 and R01 AI149620) and Brazilian National Council for Scientific and Technological Development (CNPq-404182/2019-4).